The application of the monroe doctrine to the Venezuela boundary question - Kirkpatrick, Mark (My University, 1896)
Introduction: The end of the nineteenth century means the close of one of the most eventful periods in the history of the world.
Citation: Kirkpatrick, Mark. The application of the monroe doctrine to the Venezuela boundary question. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: History; Monroe doctrine; Triumphs; Theses; Manuscripts (documents)